Pidginized English Formation by Art Shop Attendants in Seminyak Street - Kiki Cintya Yunira, Ni Putu; Triediwan, I Nyoman; Sumaryana Putra, I Komang (Udayana Journal of Social Sciences and Humanities; Vol 4 No 2 (2020): UJoSSH, September 2020, 2020)
This study  aimed at finding out forms of pidginized English which used by the shop attendants in Seminyak. The data was analyzed qualitatively. Population and Sample Techniques was based on the sociolinguistics theory, particularly the theories of Wardhaugh (1986), Holmes (1992), Hudson (1980), Todd (1984), and Quirk and Greenbaum (1985). The method of collecting data used in this data was observation, interview and questionnaire. The data was collected by note taking technique by observing the shop attendance when ever they speak English with foreign customers. The Findings showed that the forms of pidginized Englishused by the shop attendants was positive, negative, and interrogative forms. As for  the functions they used expressive, descriptive, argumentative, and signaling function.